Tradisi Pembayaran Fidyah di Kampung Wangkal dalam Perspektif Hukum Islam - Suhaeri (Musyarokah: Jurnal Hukum dan Ekonomi Islam, 2023)
ABSTRACT Honey (a liquid produced by bees) in relation to the issue of zakat has given rise to a debate among the jurists, regarding: "Is honey an object of zakat or not?" because al-Qur'an as the main source often does not explicitly explain the provisions for zakat on wealth. In connection with the above, this research aims to reveal the opinions and arguments used by 'fiqh scholars to then determine which arguments ('aqli and naqli) are stronger. This research took samples from two Imams of the mazhab, namely Imam Abu Hanifah and Imam ash-Shafi'i for two reasons, namely that both are representatives of the fuqaha' school, Imam Abu Hanifah is a rationalist school while Imam ash-Shafi'i is a mutakallimin school. The approach method used is philosophical and al-Hadith science (Tarjih bain an-Nusus). Philosophical methods are used to study evidence based on qiyas. Meanwhile, the science of al-Hadith (Tarjih bain an-Nusus) is used when studying the Naqli propositions in the form of the Prophet's hadith. The analysis method is comparative. After conducting a search through the literature of the two Imams of the sect, it was found that there were differences of opinion, Imam Abu Hanifah said that honey is the same as agricultural products for which zakat must be paid, while Imam ash-Shafi'i said that honey is not a staple food and is the same as milk which according to the agreement of the ulama does not require zakat to be paid. This is influenced by several things: 1). The differences in viewpoints between the two Imams of the sect in viewing assets for which zakat must be paid. 2). Differences in the understanding of the two Imams of the sect in understanding the messages of the Qur'an through qiyas. 3). Differences in the use of the Prophet's hadith as evidence. This research shows that the stronger opinion is the opinion of Imam Abu Hanifah because the arguments he uses point to the capacity of ma'mulun bihi (worthy of being used as a basis for religious behavior with him).